MOTIVATION RELATIONSHIP WITH CLEAN AND HEALTHY LIVING BEHAVIORS NURSING STUDENTS - Risnah Risnah; Meilinda Nur Khafifa; Nur Hidayah; Muhammad Irwan (Jurnal Kesehatan, 2021)
The campus environment is a place for students to study and their mindset should be able to apply PHBS in the campus environment and be able to apply it in everyday life. The purposed of this study was to determine the relationship between motivation and hygiene and healthy living behavior (phbs) in nursing student. This research design using quantitative with cross-sectional approach. The sample in this study were all nursing students in semester 2 with a total sample of 68 respondents. The results of the study using the Chi-Square test with a significant level of 0.05 were obtained as a result of P = 0.009, because the Pvalue <0.05, the hypothesis was accepted that there was a significant relationship between motivation and clean and healthy living behavior (PHBS) in nursing students. However, more than 20% of cells had an expected count of less than 5, which means they did not have requirements for the chi-square test, then the Fisher's Exact Test value was 0.054, which means that the p value was <0.05. So it can be concluded in this study that there is a significant relationship between motivation and PHBS clinically, but it does not have a statistically significant relationship.